An evaluation of powerlifting and weightlifting development program - Ahmad Nuruhidin; Firmansyah Putra; Okky Indera Pamungkas; Hysa Ardiyanto; Deny Pradana Saputro (Psychology, Evaluation, and Technology in Educational Research, 2018)
This study aimed to evaluate the implementation of Powerlifting and Weightlifting Development Program in Padepokan Gajah Lampung. The subjects were 30 persons, consisting of the management, the coaches, and athletes. The research used a CIPP evaluation model (Context, Input, Process, and Product). Data collection techniques were observation, interviews, and documentation. Data analysis techniques were qualitative descriptive analysis. The results showed that generally the evaluation of Powerlifting and Weightlifting Development Program in Padepokan Gajah Lampung was in good category, which described; (1) evaluation the context of development purpose had met the defined criteria, (2) input evaluation which consisted coaches, athlete and supporting facilities and infrastructure such as training qualification, had met the defined criteria standard although the exercise program was not written and reported, (3) evaluation process on the implementation of powerlifting and weightlifting program had run well. In the exercise implementation, there is a clear regular schedule of exercise, and follow the championship either in national or international level, and (4) product evaluation, generally performance, the achievement of weightlifters and powerlifters in Padepokan Gajah Lampung was excellent, which proven by the achievements achieved through national level, Asia and International.